2022
DOI: 10.1111/odi.14173
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key biomarkers related to epithelial‐mesenchymal transition and immune infiltration in ameloblastoma using integrated bioinformatics analysis

Abstract: Jackson et al., 1996). The main clinical manifestation is a progressive, painless enlargement of the jawbone, which is often diagnosed as a large tumor with cortical perforation and soft tissue invasion (Fregnani et al., 2010). Currently, surgical excision is a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…According to Santos et al [68] and the present study, CDK1 was considered a critical gene, playing a significant role in the etiology of ameloblastoma. Zhang et al [71] recently executed an integrated bioinformatics analysis to demonstrate potential biomarkers and molecular mechanisms associated with the epithelialmesenchymal transition (EMT) and immune infiltration in ameloblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Santos et al [68] and the present study, CDK1 was considered a critical gene, playing a significant role in the etiology of ameloblastoma. Zhang et al [71] recently executed an integrated bioinformatics analysis to demonstrate potential biomarkers and molecular mechanisms associated with the epithelialmesenchymal transition (EMT) and immune infiltration in ameloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…e authors used the CIBERSORT algorithm to study the immune infiltration in ameloblastoma. Zhang et al [71] reported that a total of 776 genes were deregulated in ameloblastoma, in which FN1 was upregulated and was linked to the macrophage M2 polarization. e current study had certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In the conservative approach, enucleation is included, and in the radical approach, excision and local reconstruction are considered. Its recurrence is a common complication of conservative treatment; although the conservative approach maintains the integrity of the bone with its growth pattern, it is associated with a high possibility of recurrence ranging from 55–90% [ 19 , 28 , 29 , 30 , 31 ]. To reduce these recurrences, complete bone resection with a safety margin has been considered an adequate option, mainly through marginal or segmental osteotomy for the mandible and partial or total maxillectomy for the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…The bioinformatics methods on microarray profile datasets represents an important opportunity and strategy to correlate the clinical and molecular features with the possible application of therapeutic and/or prognostic biomarkers of ameloblastoma. Through these assays, the existence of differential changes in inflammatory and immunological mechanisms, MAP kinases, and cell cycle deregulations in ameloblastoma has been determined [ 16 , 17 , 18 , 19 ]. As we mentioned above, with this large amount of information, it is possible to postulate candidates for new therapeutic alternatives, as well as to establish correlations with clinical and histological variables of this odontogenic tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as high-throughput sequencing has evolved, stratifying tumor patients by bioinformatics and machine learning approaches to explore new biomarkers has proven to be reliable and useful ( Zhang et al, 2022a ; Zhang et al, 2022b ; Sun et al, 2022 ). In the current study, we first screened differential expression ofLRGs (DE-LRGs) between EWS and normal tissues.…”
Section: Introductionmentioning
confidence: 99%